Development of plasma actuators for re-ignition of aeroengine under high altitude conditions. Issue 1 (1st February 2022) - Mehdi, Ghazanfar; Sara, Bonuso; Maria Grazia, De surname
Abstract: Re-ignition of aeroengine under high altitude conditions is of great importance to the safety and use of lean-burn engines. The present work investigated the experimental and numerical analysis of flow and re-ignition characteristics in a rectangular burner. A ring-needle type plasma actuator was developed and powered by high voltage nanopulsed plasma generator with different percentage values of amplitude voltage and frequencies. Flow visualizations by using high speed camera and Proper Orthogonal Decomposition (POD) were performed to recognize the dominant flow structures. Experimental results showed the transport effects such as induced flow with an impact on the recirculation zone near the corners of combustor, improving the mixing performance, which could be contribute to the reduction of ignition delay timings. Experimental characterization in non-reactive flow allowed the estimation of the electrical power and the optimal reduced electric field (EN) value, which was then used as input to the numerical study for the flame ignition analysis. Ignition characteristics were analyzed by coupling two different numerical tools ZDPlasKin and Chemkin. It was noticed that time required to achieve the maximum flame temperature with plasma actuation is significantly reduced in compared with autoignition timings (clean case). Maximum reduction in ignition timings was observed at inlet pressure 1 bar (3.5×10 -5 s) in respect to clean case (1.1×10 -3 s). However, as the inlet pressure is reduced, the ignition delay timings were increased. At 0.6 bar flame ignition was occurred at 0.0048s and 0.0022s and in clean case and plasma actuation case, respectively.